2011
DOI: 10.1016/j.joca.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Structured three-dimensional co-culture of mesenchymal stem cells with chondrocytes promotes chondrogenic differentiation without hypertrophy

Abstract: Summary Objective This study investigated a novel approach to induce chondrogenic differentiation of human mesenchymal stem cells (hMSC). We hypothesized that a structured three-dimensional co-culture using hMSC and chondrocytes would provide chondroinductive cues to hMSC without inducing hypertrophy. Method In an effort to promote optimal chondrogenic differentiation of hMSC, we created bilaminar cell pellets (BCPs), which consist of a spherical population of hMSC encased within a layer of juvenile chondro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
105
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 39 publications
2
105
2
Order By: Relevance
“…In vitro a structured bi-layered co-culture enhanced Previous studies have demonstrated that in vitro hypertrophy of MSCs is inhibited through co-culture with chondrocytes [50][51], with parathyroid hormone-related protein secreted by chondrocytes proposed as one mechanism by which this suppression of terminal differentiation occurs [52]. In the present study a structured bi-layered chondrogenic coculture differentially regulated the synthesis of collagen by chondrocytes and MSCs within the construct.…”
Section: Discussionmentioning
confidence: 52%
“…In vitro a structured bi-layered co-culture enhanced Previous studies have demonstrated that in vitro hypertrophy of MSCs is inhibited through co-culture with chondrocytes [50][51], with parathyroid hormone-related protein secreted by chondrocytes proposed as one mechanism by which this suppression of terminal differentiation occurs [52]. In the present study a structured bi-layered chondrogenic coculture differentially regulated the synthesis of collagen by chondrocytes and MSCs within the construct.…”
Section: Discussionmentioning
confidence: 52%
“…As we know, chondrogenic cells commonly begin hypertrophic differentiation after 21 d [28][29][30][31], and we also showed that the hypertrophic marker Col10a1 was significantly increased after 21 d of chondrogenic differentiation; thus, miR-455-3p might be involved in the acceleration of early chondrogenesis, but not hypertrophic differentiation.…”
Section: Discussionmentioning
confidence: 67%
“…MSCs are multipotent stem cells primarily isolated from bone marrow. These cells differentiate into several cell lineages including osteogenic and chondrogenic [8,9]. More recently described induced pluripotent stem cells (iPSCs) have the potential to differentiate into somatic cells, including chondrocytes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%